Cerebellar pilocytic astrocytoma in childhood: Investigating the long-term impact of surgery on cognitive performance and functional outcome. (18th August 2018) - Pletschko, Thomas; Felnhofer, Anna; Lamplmair, Doris; Dorfer, Christian; Czech, Thomas; Chocholous, Monika; Slavc, Irene; Leiss, Ulrike
ABSTRACT: Objective : Previous studies differ regarding the long-term effects of surgically removed pediatric cerebellar pilocytic astrocytomas (CPA). Thus, the aim of this study was to investigate the long-term impact on neurocognitive and functional outcome and to analyze age as an influencing factor. Methods : Fourteen CPA patients were compared to the age norm and to a group of 14 high-achieving peers regarding cognitive functioning, health-related quality of life (HRQoL), and stress regulation. Mean follow-up time after diagnosis was 13.29 years (range: 3–21 years). Results : Patients showed satisfactory academic achievement and did not differ from the norm except for the bodily dimension of HRQoL. However, there were marked differences in specific neurocognitive functions between patients and high achievers. Age at diagnosis did not influence neurocognitive outcome. Conclusion : CPA patients treated with surgery only seem to have a favorable long-term outcome, yet, in comparison with high achievers specific cognitive impairments become apparent.